LAW AND ECONOMICS: DISCUSSIONS CONCERNING THE 2002 BRAZILIAN CIVIL CODE AND COVID-19 - Novaes Hegenberg, FlÃ¡vio Edmundo (2020)
This text is a discussion concerning economic and legal â€œpowersâ€ in Brazil. The context of crisis caused by the COVID-19 pandemic makes this discussion necessary. The overall context adopted here is one of Law and Economics. A brief discussion is made about the contemporary Liberal State. Some ideas concerning the 20th century workings of the state (if the state is Â´social` or if it is Â´minimumÂ´) is also analysed. Some reality is offered by providing numbers collected from The World Bank. Information regarding COVID-19 as a global cause for economic crises is given. Within the text, Article 421-A of the Brazilian Civil Code is discussed. Some concluding remarks shed some light regarding what could be done to improve things in Brazil.